Spatial Plan of Wisma Athletes as A Defense in The Era of The Covid-19 Pandemic - Diva Miftachul Rahma; Firauz Ihsan F (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
In this era of the COVID-19 pandemic, there are many things that need to be watched out for and also need to be prepared. The role of the government as one of the leaders of a country needs to have a plan to overcome these problems. One of the efforts made by the government is to create a Covid-19 emergency hospital by converting the Kemayoran and Pademangan Wisma Athletes. The selection of this athlete's home is considered to be able to accommodate patients affected by COVID-19. But not only that, every room in this emergency hospital is a shield for every patient. Each room in the athlete's house has its own role and function, not least as a means of defense for every patient, to support this, the use of descriptive and narrative analysis is to explain how the architectural layout in the athlete's house and also use narrative analysis techniques to focus on an idea that can be developed into a related part. From the results of this analysis, it is also expected to get results to provide new knowledge, about how patients in the athlete's house become a means of defense for themselves.